Gerakan Separatis dan Dampaknya Terhadap Pengembangan Demokrasi - Bambang Cipto (Universitas Islam Indonesia, 2003)
A long Asia continent, from Turk, Indonesia, up to Papua New Guinea, believed as the fertile land for the seeds of separatism. The keywords for such problem is actually the injustice. Means, injustice between majority and minority, also, injustice between big countries and the small ones. The solution needed is, democratization in the mean of the ability of the government to accommodate the needs of all people. When the attention of the government is only addressed for particular group of people, the spirit for separatisms is absolutely cannot be extinguished.